GeoGebra-based Scaffolding of a Prospective Mathematics Teacher's Learning While Exploring the Properties of Chord and Tangent in Circle - Candaş Uygan; Gülay Bozkurt (Anı Publishing, 2019)
The aim of this study is to investigate GeoGebra-based scaffolding and the reasoning processes of a prospective mathematics teacher while exploring chord and tangent's relations with centre point in circle within the scope of a geometric construction problem in GeoGebra. In this study, qualitative paradigm is adopted and a task-based interview is conducted with a prospective mathematics teacher enrolled in a mathematics teacher education program at a state university located in central Turkey. During the interview, the participant was given a task about construction of the centre point of a circle with different strategies in GeoGebra. Data were collected through video-camera looking at the participant's working environment and screen recorder software. The participant's reasoning processes, GeoGebra-based scaffolding needed during the task and also used dragging modalities were analysed. GeoGebra-based scaffolding consisted of three dimensions: the support provided by the software tools and also the operational and mathematical support by the interviewer. The findings of this study indicated that GeoGebra-based scaffolding became an effective way to support the prospective teacher's abductive, inductive and deductive reasoning processes in construction tasks and enabled her to discover various properties of chord and tangent in circle.